The genes involved in asthma with the treatment of human embryonic stem cell-derived mesenchymal stem cells. (March 2018) - Lin, Yong-Dong; Fan, Xing-Liang; Zhang, Hong; Fang, Shu-Bin; Li, Cheng-Lin; Deng, Meng-Xia; Qin, Zi-Li; Peng, Ya-Qi; Zhang, Hong-Yu; Fu, Qing-Ling
Highlights: Human embryonic stem cell derived mesenchymal stem cells (hESC-MSCs) successfully relieved the symptoms of asthma and suppress allergic inflammation in mouse model. hESC-MSCs modulated eosinophils, Th2 cells and promoted Treg cells in airway allergic inflammation. Ccl11, Ccl24, Il13, Il33 and Ear11 were involved in the process of hESC-MSC immunomodulation. Abstract: Background: Asthma is affecting more than 300 million people worldwide, which represents the most common chronic disease among children. We previously found that mesenchymal stem cells (MSCs) derived from induced pluripotent stem cells (iPSCs) modulated the immune response on Th2-mediated asthma in vivo and in vitro . This study further evaluated the immunomodulatory effects of MSCs from human embryonic stem cells (hESCs) on asthma. Methods: Multipotent hESC-MSCs were obtained using a feeder-free method. The hESC-MSCs were analysed for the expression of stem cell surface markers by flow cytometry, their differentiation potentials were analysed using in vitro trilineage differentiation methods hESC-MSCs were transplanted into the murine model with ovalbumin (OVA)-induced airway allergic inflammation. The expression levels of allergic related genes were measured by the mRNA PCR arrays. Results: The hESC-MSCs expressed classical MSC markers and held the capability of differentiation into multiple mesoderm-type cell lineages. hESC-MSCs were able to suppress allergic inflammation by modulating Th2 cells and eosinophils in the mice, and reversed the reduction of regulatory T cells. By using PCR array, 5 mRNAs- chemokine (C-C motif) ligand 11 ( Ccl 11), Ccl24, interleukin13 ( Il 13), Il 33 and eosinophil-associated, ribonuclease A family, member 11 ( Ear 11) were identified the most relevant in murine airway allergic inflammation and hESC-MSCs treatment. Conclusions: The therapeutic effects of hESC-MSCs were identified in the murine model of airway allergic inflammation with key mRNAs involved. This study will provide a better understanding regarding the mechanisms underlying hESC-MSCs therapeutic application in airway allergic inflammation.